Erythrocytes Induce Vascular Dysfunction in COVID-19 - Mahdi, Ali; Collado, Aida; Tengbom, John; Jiao, Tong; Wodaje, Tigist; Johansson, Niclas; Farnebo, Filip; Färnert, Anna; Yang, Jiangning; Lundberg, Jon O.; Zhou, Zhichao; Pernow, John (JACC. Basic to translational science, 2022)
[Display omitted] •Patients hospitalized for COVID-19 display marked impairment in endothelial function, which is persistent following recovery from the acute infection.•RBCs from patients with COVID-19 impair vascular function through mechanisms involving increased arginase 1, ROS and IFNγ, and reduced NO bioactivity.•These data advance our understanding in COVID-19–associated vascular injury with a clear involvement of RBCs.•Targeting these mechanisms might provide a novel therapeutic strategy to alleviate vascular injury in patients with COVID-19. Current knowledge regarding mechanisms underlying cardiovascular complications in patients with COVID-19 is limited and urgently needed. We shed light on a previously unrecognized mechanism and unravel a key role of red blood cells, driving vascular dysfunction in patients with COVID-19 infection. We establish the presence of profound and persistent endothelial dysfunction in vivo in patients with COVID-19. Mechanistically, we show that targeting reactive oxygen species or arginase 1 improves vascular dysfunction mediated by red blood cells. These translational observations hold promise that restoring the redox balance in red blood cells might alleviate the clinical complications of COVID-19–associated vascular dysfunction.